Teaching Reading Comprehension through Visualization Strategy - Saftiah, Fitri; Zulianti, Hajjah; Febriyanti, Febriyanti (STKIP PGRI Bandar Lampung, 2024)
This research aimed to know the influence of visualization strategy towards students' reading comprehension on narrative text. The writer used quantitative method and categorized the research as quasi experimental method. The population was 246 from 8 classes. The writer used Cluster Random Sampling Technique in taking the sample. There were 2 classes as a sample. X1 was an experiment class and X2 was a control class. The experiment class consisted of 32 students and control class consisted of 34 students. The main technique in measuring students’ reading comprehension was multiple choice which consisted of 40 items with 5 options a, b, c, d and e. The score of each item is 2,5 for correct answer. In calculating the data analysis, the writer used t-test formula. Based on the data analysis, the average score of experimental class was 81,94 and the average score of control class was 73,25 which means the average score of experimental class was higher than control class. The writer got that Ha was accepted. It was obtained that ttest = 3,73 and ttable 0,05 = 2,00 and 0,01 = 2,66 (3,73 > 2,00 < 2,66). It means that there was a significant influence of Visualization strategy towards students’ reading comprehension on narrative text at the tenth grade of SMA Negeri 8 Bandar Lampung in 2022/2023.